Comparison of survival at adult versus pediatric treatment centers for rare pediatric tumors in an adolescent and young adult (AYA) population in the state of Georgia. Issue 3 (12th November 2014) - Cash, Thomas; Qayed, Muna; Ward, Kevin C.; Mertens, Ann C.; Rapkin, Louis
<x xml:space="preserve">Abstract</x> Background The type of treatment center where 15–21‐year‐old adolescent and young adult (AYA) patients with rare pediatric tumors achieve their best clinical outcome is unknown. Procedure We performed a retrospective analysis using the Georgia Cancer Registry (GCR) of 15–21‐year old patients with a malignant, rare pediatric tumor diagnosed during the period from 2000–2009. Patients were identified as being treated at one of five Georgia pediatric cancer centers or at an adult center. Data were analyzed for 10 year overall survival, patient characteristics associated with death, and patient characteristics present at diagnosis associated with choice of treatment center. Results There was a total of 479 patients in our final study population, of which 379 (79.1%) were treated at an adult center and 100 (20.9%) were treated at a pediatric center. Patients treated at an adult center had a 10 year overall survival of 86% compared to 85% for patients treated at a pediatric center (P = 0.31). Race and poverty were not significantly associated with death. Patients with nasopharyngeal carcinoma (OR = 7.38; 95% CI = 2.30–23.75) and 'other carcinomas' (OR = 2.64; 95% CI = 1.25–5.60) were more likely to be treated at a pediatric center. Patients with higher‐stage disease (OR = 4.24; 95% CI = 1.71–10.52) and higher poverty (OR = 2.32; 95% CI = 1.23–4.37) were also more likely to be treated at a pediatric center. Conclusion Our data suggest that there is no difference in survival for 15–21‐year old patients with rare pediatric tumors when treated at an adult or pediatric center. Pediatr Blood Cancer 2015;62:456–462. © 2014 Wiley Periodicals, Inc.